Globuloverruca spongophila gen. nov., sp. nov. a sponge-associated verrucid (Crustacea: Cirripedia: Thoracica) from Easter Island, with discussion on the morphology of the plate tubules - Young, Paulo S. (Zootaxa, 2004)
Globuloverruca spongophila gen. nov., sp. nov., associated with sponges, is described from Easter Island, southeastern Pacific. It presents morphological adaptations related to the association including an elongated carina and rostrum and the presence of denticles and stout setae on the distal articles of anterior cirri. The presence of tubules in the plates of Verruca and Globuloverruca is discussed.